Solvent-free valorization of sugarcane bagasse fibers into nitrogen-doped microporous carbons: Efficient contenders for selective carbon dioxide capture - Urooj Kamran; Nasir Shezad; Soo-Jin Park; Kyong Yop Rhee; Shujie You; Farid Akhtar (Journal of CO2 Utilization)
Nitrogen-doped porous carbons have been widely explored for CO₂ storage and separation, but expensive precursors and intricate synthetic approaches often limit their practical deployment. Here, we report a facile, one-step, solvent-free method to design nitrogen-doped microporous carbons (SBF-BC-KMx) for efficient CO₂ capture from sugarcane bagasse fibers (SBF) as a low-cost precursor. Melamine and KOH were used as a nitrogen-doping source and an activator, respectively. The specimen (SBF-BC-KM0.5), prepared with optimized melamine loading, possessed efficient textural features, including a specific surface area (SSA) of 1138 m² g⁻¹ , a micropore volume of 0.396 cm³ g⁻¹ , high concentration of ultra-micropores (<0.6 nm) (89 %) and high content of pyrrolic-N functionality (35 %). These properties enhanced the CO₂ capture performance, achieving 244.4 mg g⁻¹ at 273 K, 170.0 mg g⁻¹ at 293 K and 1 bar, and 351.5 mg g⁻¹ at 293 K and 10 bar. The optimized material exhibited a moderate isosteric heat of adsorption and an effective CO₂/N₂ selectivity at 293 K. The high ultra-micropore density significantly boosted CO₂ uptake and maintained stable CO₂ uptake over five adsorption cycles. Overall, this work devoted efforts to sustainable environment, biowaste management, and possible practical applicability of designed adsorbent for CO2 storage.